Analisis Gaya Kepemimpinan Transformasional dan Pengaruhnya Terhadap Kinerja Aparat Desa Melalui Perilaku Inovatif sebagai Variabel Intervening di Kecamatan Sekernan Muaro Jambi - Kurniawan, Dodi; Adriani, Zulfina; Wediawati, Besse (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Research This study aims to examine the effect of transformational leadership on agency performance. The aim of this research is to explain and analyze the effect of transformational leadership style on the performance of village officials through innovative behavior in Sekernan Muaro Jambi District. The population of this research is the village government in 15 villages in Sekernan Muaro Jambi district. The sample size used was 105 respondents with a purposive sampling method. The analysis technique used is path analysis using the SmartPLS approach. The research results show that (1). Transformational leadership style has a positive and significant effect on innovative behavior (2). Innovative behavior has a positive and significant effect on the performance of village officials (3). Transformational leadership style has a positive and significant effect on the performance of village officials, and (4) Transformational leadership style has a positive and significant effect on the performance of village officials through innovative behavior as an intervening variable